Efectos de un programa de ejercicios coordinativos en la técnica del estilo libre en la Categoría Infantil - Sánchez Carrión, Andrea Teresa (2025)
This study examined the effect of a motor coordination-focused exercise program on freestyle swimming techniques in children. The intervention was administered over 24 sessions to a group of 17 participants, using the SWOLF test as an indicator of efficiency. Comparative results between the initial and final evaluations showed significant improvements in technical performance and aquatic movement economy. Based on these results, coaches and trainers working with young swimmers are encouraged to incorporate targeted motor coordination exercises into their programs to enhance technique and efficiency during the early stages of skill development.